Measurement and influencing factor analysis of the matching degree between agricultural scientific and technology innovation and rural industry integration under the sustainable background - Yao, Sheng; Wang, Yuanyuan; Wu, Guosong (Frontiers in Sustainable Food Systems, 2024)
Agricultural scientific and technological innovation and rural industry integration are the key contents of promoting agricultural and rural modernization in China. This study empirically analyzed the matching relationship between the two and its influencing factors, and found that the matching degree between agricultural scientific and technological innovation and rural industry integration in China showed a steady upward trend in the sample period. Both China as a whole and all regions completed the upgrading from moderate to high matching in the sample period, The performance of each region is also excellent. In 2020, the matching degree of 28 regions will enter a high matching range. The implementation of the rural revitalization policy will help to improve the matching degree between China’s agricultural scientific and technological innovation and rural industrial integration. The scale of rural financial development and the matching degree of lagging one period also have a significant positive impact on the improvement of the matching degree. This study further proposes relevant policy recommendations from improving the supply level of agricultural scientific and technology innovation, enhancing the adaptability between supply and demand of agricultural scientific and technology innovation, improving the policy support system, and optimizing the financial security system.